Identifying Factors Shaping Help-Seeking Behaviors in Individuals With Depression - Hrivnáková, Zuzana; Tremblay, David; Leppik, Taavi (KMAN Counseling & Psychology Nexus, 2026)
The objective of this study was to identify the psychological, social, and systemic factors influencing help-seeking behaviors among individuals living with depression. This qualitative study employed a phenomenological design to explore the lived experiences of adults diagnosed with depression. A purposive sampling strategy was used to recruit 20 participants residing in Canada, representing diverse gender, age, and socioeconomic backgrounds. Data collection consisted of semi-structured, in-depth interviews lasting 45–75 minutes, conducted either in person or via secure video conferencing platforms. Interviews were transcribed verbatim, anonymized, and analyzed using NVivo software. Thematic analysis guided data interpretation, following iterative coding, constant comparison, and refinement of conceptual categories. Two researchers independently coded initial transcripts to enhance credibility and resolve discrepancies through discussion, while data collection continued until theoretical saturation was reached. Ethical considerations, including informed consent and confidentiality safeguards, were strictly observed throughout the research process. Analysis revealed three overarching themes shaping help-seeking: (1) personal and psychological influences, including internalized stigma, emotional avoidance, cognitive readiness, and the role of crisis thresholds; (2) social and relational contexts, encompassing family encouragement, cultural norms, peer influence, community stigma, and relationship dynamics; and (3) structural and systemic conditions, including financial barriers, service accessibility, system navigation challenges, provider fit, and trust in healthcare institutions. Across participants, help-seeking behavior emerged as a dynamic and multilayered process shaped by the interaction of individual vulnerability, sociocultural expectations, and systemic affordances or constraints. The study concludes that help-seeking for depression is influenced by a complex interplay of emotional, social, and structural factors, highlighting the need for culturally sensitive interventions, improved accessibility, and system-level strategies to reduce stigma and facilitate timely engagement with mental health services.